Delayed miniature pulpotomy in a symptomatic mature molar - Mohsen Ramazani; Saeed Asgary (Wolters Kluwer Medknow Publications, 2018)
This case report describes miniature pulpotomy (MP) with calcium-enriched mixture (CEM) cement, 1 week after carious pulpal exposure of a symptomatic mature molar. A 24-year-old woman was referred with complaining of severe lingering pain on the second upper left molar; a dental history revealed that the tooth had been prepared 1 week ago, but on pulp exposure, her dentist just dressed the cavity. After anesthesia/isolation in the same session, the temporary restoration was removed, the previously pulpal exposure was observed, and MP was carried out. Hemorrhage was effectively controlled using 5.25% NaOCl, the clot free pulpal wound was completely covered employing CEM cement, and the cavity was permanently restored by resin composite. The patient's pain gradually relieved within 24 h. The tooth was functional and able to respond to vitality tests in regular clinical follow-ups. At 15-month follow-up, a dentinal bridge was observed under the capping biomaterial, radiographically; moreover, no calcification or apical pathosis was detected. MP with CEM cement might be a treatment option for the management of exposed dental pulp with a clinical diagnosis of irreversible pulpitis, although further trials with larger sample size and longer follow-ups are recommended.